Mouse embryonic stem cells: The establishment of the system to produce differentiated cell types in vitro - Paz, Ana Helena da Rosa; Rief, Stephanie; Santos, Diógenes Santiago; Wolf, Eckhard; Prelle, Katja; Cirne Lima, Elizabeth Obino (Acta Scientiae Veterinariae, 2018)
During the last few years, embryonic stem (ES) cells have been a new tool in cell biology which is very promising for the scientific community to develop new cell therapies. ES cells are the only cell type that can differentiate into derivates of the three primary germ layers, not only in vivo but also, and most important, in vitro. This so-called pluripotency has resulted in the field of stem cell technology going into overdrive, and the establishment of many protocols for optimal maintenance, culture, genetic transfection and in vitro differentiation. The first pluripotent cells had been derived from teratocarcinomas, maligne tumors, and showed some disadvantages. Therefore later embryonic stem cells, and now adult stem cells are getting special attention from the scientists. In this study, we established for the first time in our country, the prolonged culture of undifferentiated ES cells in vitro and the pointed induction of cell differentiation into specific cell types. It is the result of an international collaboration program supported by Brazil and Germany, CAPES and DAAD (PROBRAL). The well-established routine should be clearly demonstrated by the continuous culture and propagation of several mouse ES lines in vitro under specific culture conditions preventing differentiation. On the other hand, these ES cells were exposed to defined differentiation induction systems to obtain specialized cells as cardiogenic, neurogenic and myogenic cell types. This demonstrates the successful procedure to induce ES cell line differentiation. In this study, we established both routine systems, with and without differentiation. This results gave us competence and possibility to develop a series of different scientific approaches.